The Urban Avifauna of Kuching, Borneo, and the possible impact of cats on its structure - Hong, Arleen; Jayasilan, Mohd-Azlan (The Kukila Editorial Team, 2018)
Urban landscapes have depauperate avifaunas, but there have been few studies of urban bird communities in Southeast Asia. Domestic cats can attain very high densities in urban environments, and are known to have detrimental effects on local avian assemblages. The aim of this study was to describe the urban bird assemblage of Kuching, an equatorial city in Borneo, and to investigate its potential relationship with the abundance of cats. The density of birds and domestic cats was examined in ten discrete urban areas from November 2014 to April 2015 using line transects. A total of 1,844 bird observations were made, involving 27 species. Bird species richness and diversity were negatively related to cat density (R2 = 0.41 and 0.43, respectively), but cat density did not significantly affect bird density (R2 = 0.032). Bird species richness was strongly correlated with the size of urban areas (R2 = 0.76, P = 0.001) suggesting that larger areas offer additional habitat or niches (e.g. street trees, parks, waterways), which in turn support more species. Reduction of habitat heterogeneity and type of surrounding matrix, as well as the presence of abundant introduced predators may play important roles in structuring the composition and population dynamics of this urban bird community. Urban areas do have some biodiversity conservation value, but the challenge is to enhance this value through better planning.